Science Communication Online Engaging Experts and Publics on the Internet - Mehlenbacher, Ashley (The Ohio State University Press, 2019)
As science communication has moved online, a range of important new genres have emerged: crowdfunding proposals, blogs, microblogs, databases, and more. Rhetorics of Science Online takes up these genres to explore how scientists are adapting their communications, how publics are increasingly involved in science, and how boundaries between experts and non-experts continue to erode.